Not only grades. An integrative approach over school achievement - Lisimberti, Cristina; Montalbetti, Katia (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2016)
The educational success, which means more than attending school with good performance, is a goal for the whole society. The research takes rise from the partnership between CeRiForm and Portofranco, a non-profit organization which provides a service to students having difficulties in their school learning in Milan. In this association aid in facing negative performances at school is considered as a part of a global educational process aiming to support student personal growth at any level. The explorative research aims to underline the impact of Portofranco experience in giving educational support to student development as a whole person, with particular attention to the social dimension. Thanks to this explorative study some interesting data have been pointed out useful to highlight the main dimensions of this complex phenomenon; at the same time the research has put in evidence other questions which need to be analyzed in future empirical studies.